2010
DOI: 10.1111/j.1758-2229.2010.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens BBc6R8 type III secretion mutants no longer promote ectomycorrhizal symbiosis

Abstract: The Mycorrhiza Helper Bacterium (MHB) Pseudomonas fluorescens BBc6R8 promotes the ectomycorrhizal symbiosis between Douglas fir roots and Laccaria bicolor. In this study, we identified a non-flagellar type III secretion system (T3SS) in the draft genome of BBc6R8 similar to that described in the biocontrol strain P. fluorescens SBW25. We examined whether this T3SS plays a role in the BBc6R8 mycorrhizal helper effect by creating a deletion in the rscRST genes encoding the central channel of the injectisome. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Surprisingly, evidence for the translocation of T3SS effectors into the fungal cytoplasm does not exist; however, two recent studies employing T3SS mutants suggested that these systems may play a role in BFIs (87,206). Cusano et al (87) demonstrated that a disruption of the T3SS of Pseudomonas fluorescens BBc6R8 abolished its mycorrhizal helper effect, although whether the plant of the fungus was the T3SS target is unknown. Lackner et al (206) found that the disruption of a T3SS gene cluster in the endobacterium Burkholderia rhizoxinica resulted in a reduced intrahyphal survival of the bacterium and a failure to elicit the sporulation of the Rhizopus microsporus host.…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, evidence for the translocation of T3SS effectors into the fungal cytoplasm does not exist; however, two recent studies employing T3SS mutants suggested that these systems may play a role in BFIs (87,206). Cusano et al (87) demonstrated that a disruption of the T3SS of Pseudomonas fluorescens BBc6R8 abolished its mycorrhizal helper effect, although whether the plant of the fungus was the T3SS target is unknown. Lackner et al (206) found that the disruption of a T3SS gene cluster in the endobacterium Burkholderia rhizoxinica resulted in a reduced intrahyphal survival of the bacterium and a failure to elicit the sporulation of the Rhizopus microsporus host.…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…The heterologous expression of T3SS effector proteins from a range of plant-and animal-pathogenic bacteria in S. cerevisiae has been used successfully to identify their potential cellular functions (368). Surprisingly, evidence for the translocation of T3SS effectors into the fungal cytoplasm does not exist; however, two recent studies employing T3SS mutants suggested that these systems may play a role in BFIs (87,206). Cusano et al (87) demonstrated that a disruption of the T3SS of Pseudomonas fluorescens BBc6R8 abolished its mycorrhizal helper effect, although whether the plant of the fungus was the T3SS target is unknown.…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…Apart from its physical and chemical characteristics, which differ from those of the rhizosphere (26, 28), the ectomycorrhizosphere is characterized by diverse fungal and bacterial communities that inhabit the same environment. Consequently, the functioning of the ectomycorrhizal symbiosis is influenced by each partner of the ectomycorrhizal (ECM) complex (6,8, 9).Cultivation-dependent and -independent studies have demonstrated the structuring effect of the mycorrhizal fungi on the soil bacterial communities. They revealed that the bacterial communities colonizing the ectomycorrhizal roots differed from those of uncolonized roots and that the ectomycorrhizal species differentially impacted the structure of ectomycorrhizosphere bacterial communities (2,11,12,22,35,37).…”
mentioning
confidence: 99%
“…Apart from its physical and chemical characteristics, which differ from those of the rhizosphere (26,28), the ectomycorrhizosphere is characterized by diverse fungal and bacterial communities that inhabit the same environment. Consequently, the functioning of the ectomycorrhizal symbiosis is influenced by each partner of the ectomycorrhizal (ECM) complex (6,8,9).…”
mentioning
confidence: 99%
“…Many studies have focused on the physiological aspects of mycorrhizal interactions between plant root systems and fungi. The mechanisms of MHB stimulating mycorrhiza formation, however, still remain unclear (Deveau et al 2007;Cusano et al 2011). Especially, the molecular mechanisms of the interaction between MHB and mycorrhiza fungi are poorly understood.…”
Section: Introductionmentioning
confidence: 99%